(untitled) (Global Journal of Management and Business Research, 2022)
The demographic misrepresentation in organizations is a key business and social issue across the world in establishments of all kinds. In many institutions and businesses there is a conscious effort to improve diversity, but understanding and calculating what constitutes a diverse workforce is challenging. The purpose of this paper is to provide methodology for calculating diversity parameters for race and ethnicity based on country and business specifics.